Differential Diagnosis and Hospital Emergency Management for Fastlane Treatment of Central Nervous System Infection Under the COVID-19 Epidemic in Changsha, China - Yang, Haojun; Chi, Yunfang; Chen, Zhuohui; Fan, Yishu; Wu, Haiyue; Hu, Xinhang; Wu, Tong; Xiao, Bo; Zhang, Mengqi (Frontiers in Neurology, 2020)
Importance Corona Virus Disease 2019 (COVID-19) has a long latent period, strong infectivity, and nonspecific symptoms and signs in the upper respiratory tract. Some initial neurological symptoms appear including dizziness, headache, seizures, slurred speech, disturbance of consciousness, and limb paralysis among few COVID-19 patients, which shares similar manifestations with central nervous system (CNS) infection. Improving the diagnostic efficiency of suspected CNS infection patients on the basis of preventing and controlling COVID-19 plays a key role in preventing nosocomial and cross infections. This study intends to formulate a hospital emergency management system of fast lane treatment of CNS infection for epidemic prevention and control, aiming at providing references and guidelines for the government and medical institutions to improve the efficiency of treating CNS infection patients in the clinical practice during COVID-19. Observations This study formulated framework of fast lane treatment of CNS infection based on the cooperation of resources and experience, aiming at the key and difficult problems faced by the hospital emergency management system during the COVID-19 outbreak in Changsha, China. The main problem of formulating the hospital emergency management system is efficiently identifying whether CNS infection was caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). The framework improves the efficiency of diagnosing and treating CNS infections by standardizing the diagnosis and treatment process of patients in emergency observation and strengthening the management of inpatient wards, aiming at assisting medical staff during clinical practice. Conclusions and Relevance The hospital emergency management system of fast lane treatment of CNS infection for epidemic prevention and control of the COVID-19 outbreak is a professional and multisystem project, which needs the cooperation of various resources and the experience of clinical leadership.